Selecting the Technical Solutions for Thermal and Energy Rehabilitation and Modernization of Buildings. (2016) - Giurca, Ioan; Aşchilean, Ioan; Naghiu, George Sebastian; Badea, Gheorghe
Abstract: This article aims to describe a method regarding the selection of technical solutions for thermal and energy rehabilitation and modernization of buildings, for this purpose the TOPSIS method being used. In this article we also included a case study concerning the use of TOPSIS method in case of energy audit for buildings. The article concludes that TOPSIS may be used for energy audit projects for buildings. Based on the article's conclusions, we are making proposals in order to improve the actual legislation in the field of building energy audit.